Porous material for separating and forming ethylene and propylene

Through the metal-organic frame materials synthesized by cheap organic ligands and metal ions, the high energy consumption and safety hazards of traditional ethylene propylene separation methods are solved, and high-efficiency ethylene propylene separation and preferential adsorption of MTO products are achieved, with good thermal stability and industrial application prospects.

CN119186514APending Publication Date: 2024-12-27ZHEJIANG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411284752.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional ethylene propylene separation methods such as high-energy low-temperature distillation and alkaline washing have safety hazards and resource shortages, and existing adsorbents are not effective when separating ethylene propylene.

Method used

The metal organic frame material prepared by solvent-thermal synthesis based on the inexpensive organic ligand formic acid and metal ions Ni, Co, Mg, and Mn is used to form a molded porous material with polyether sulfone through phase conversion method to achieve selective adsorption and separation of ethylene propylene.

Benefits of technology

The material exhibits high propylene adsorption ability under low pressure conditions, which is better than ethylene, and can effectively separate MTO products, have good thermal stability and recycling capabilities, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186514A_ABST
    Figure CN119186514A_ABST
Patent Text Reader

Abstract

The invention discloses a porous material, a formed porous material and application of the porous material and the formed porous material in adsorption separation of ethylene and propylene. The porous material is one or more metal organic framework materials with the structural general formula of M3 (HCOO) 6, wherein M is Ni, Co, Mg or Mn. The preparation method of the formed porous material comprises the following steps: uniformly mixing the porous material, polyether sulfone and N, N-dimethylformamide by adopting a phase inversion method, and transferring the mixture into absolute methanol to form the formed porous material. The porous material has the advantages of cheap synthetic raw materials, low cost, simple synthetic method, large-scale synthesis and large bulk density. In the forming process, the separation effect of the material on C3H6 and C2H4 is almost not influenced, the formed porous material effectively relieves the problem of pore channel blockage caused by powder, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical separation, in particular to ethylene and propylene separation and a formed porous material. Background Art

[0002] Ethylene (C2H4) and propylene (C3H6) are the most important chemical raw materials in the global petrochemical industry and have been widely used in the manufacture of various chemicals, such as synthetic fibers, rubber, polyvinyl chloride and other organic chemicals.

[0003] As important raw materials for downstream manufacturing, the global demand for propylene (C3H6) and ethylene (C2H4) is increasing. However, traditionally, C3H6 and C2H4 are mainly produced through crude oil cracking or dehydrogenation processes. Since crude oil is a non-renewable resource, finding other preparation methods is of great significance to alleviate resource problems.

[0004] The methanol to olefins (MTO) process is an effective method for preparing C2H4 from coal and natural gas. It can not only realize the conversion of coal chemical products into petrochemical products and alleviate the resource shortage problem caused by dependence on crude oil cracking; at the same time, the use of the MTO process to consume methanol to produce olefins as an entry point can effectively alleviate the problem of methanol overproduction.

[0005] In the MTO process, 51.10wt% C2H4 and 20.91wt% C3H6 are produced. The purity of C2H4 and C3H6 obtained by the MTO process cannot meet the requirements of industrial applications. The traditional separation of C3H6 / C2H4 mixtures is energy-intensive low-temperature distillation. In addition, the traditional separation method of MTO products is alkaline washing, but this process produces a large amount of butter, which affects the safe use of equipment. Compared with these methods, adsorption separation using adsorbents is safer and more energy-efficient.

[0006] Metal organic frameworks (MOFs) are a type of porous material formed by the self-assembly of metal ions and organic ligands through coordination bonds. They have the characteristics of large specific surface area, finely regulated pore size and pore environment, and have potential application prospects in gas adsorption and separation.

[0007] Formic acid (HCOOH) is a common and inexpensive organic ligand, while inorganic salts such as nickel, cobalt, manganese, and magnesium are also common and inexpensive metal salts. The formic acid series organic metal framework materials synthesized by solvent thermal synthesis have low cost and simple synthesis operation. Secondly, the formic acid series ultra-microporous porous materials obtained have a high packing density. The patent specification with publication number CN114409498A discloses a method of reacting HCOOH with metal ions Co 2+ 、Ni 2+ Mg 2+The synthesized microporous material is used as an adsorbent to separate isomers of C8 aromatic hydrocarbons. The patent specification with publication number CN113527030A discloses a method for separating cyclopentane and neohexane by adsorption using a porous metal organic framework material formed by coordination bonds of Fe, Co, Ni, Cu, Mg, Mn or Zn and formic acid. Summary of the invention

[0008] In a first aspect, the present invention provides a method for preparing a molded porous material having ethylene-propylene adsorption and separation capabilities, comprising: using a phase inversion method, mixing a porous material, polyethersulfone and N,N-dimethylformamide (DMF) and transferring the mixture to anhydrous methanol to form a molded porous material;

[0009] The porous material is one or more metal organic framework materials with a general structural formula of M3(HCOO)6, wherein M is Ni, Co, Mg or Mn.

[0010] The porous material described in the present invention is a metal organic framework material. An exemplary structure is shown in Figure 1 The general structural formula is M3(HCOO)6, which is composed of an organic ligand formic acid (HCOOH) connected by a single bond between the O atom and M 2+ Ionic coordination connection formation, specifically: metal ion M 2+ The oxygen atoms single-bonded to formic acid are connected via coordination bonds, where each metal ion forms six coordinations with the oxygen atom, resulting in an octahedral coordination geometry bridged by formic acid, constructing MM4 tetrahedral nodes centered on M. By sharing vertices, these tetrahedral nodes form a zigzag channel.

[0011] The preparation process of this metal organic framework material is to use cheap formic acid as an organic ligand and a series of metal ions through solvent thermal synthesis. The raw materials of the prepared materials are cheap and easy to obtain, the experimental operation is simple, the synthesis conditions are mild, the post-treatment is easy, and it can be mass-produced. Because the prepared porous material has a pore size that is compatible with propylene, and there are a large number of O sites in the pores that can firmly adsorb propylene, under low pressure conditions, the pores of the porous material will be quickly occupied by propylene, and it has an extremely high propylene stacking density. Through the single-component adsorption isotherm, it can be found that under low pressure conditions (5kPa), the adsorption amount of propylene in Co3(HCOO)6 can reach 82.4cm 3 / cm 3Therefore, the metal organic framework material disclosed in the present invention has a much stronger adsorption capacity for propylene than ethylene, and can achieve preferential adsorption of propylene to achieve the purpose of separating MTO products. The porous material and the polyethersulfone adhesive can be used to obtain particles with a particle size of 1 to 5 mm through a phase inversion method, which not only alleviates the problem of pipeline blockage caused by powder, but also the porous material after molding maintains the performance of the porous material in separating MTO products. The material structure and adsorption performance are stable, recyclable, and have good thermal stability, and have good industrial application prospects.

[0012] The present invention uses polyethersulfone as an adhesive. The inventor has found that if hydroxypropyl cellulose (HPC), polyvinyl butyral (PVB), polyvinylidene fluoride (PVDF) and other adhesives are used to replace polyethersulfone, the result will be that the molding cannot be performed, or the material loses its original ethylene propylene adsorption separation performance after molding. In some preferred examples, the amount of the polyethersulfone is 5% to 10% of the sum of the mass of the porous material and the polyethersulfone.

[0013] In the method for preparing the shaped porous material, the transfer may be carried out by dropping.

[0014] In some embodiments, the particle size of the shaped porous material is 2 to 3 mm.

[0015] The porous material of the present invention has a high adsorption capacity for propylene and ethylene; at the same time, the adsorption capacity for propylene is stronger than that for ethylene, and can be used for separating MTO products.

[0016] The present invention does not specifically limit the preparation method of the porous material, and the prior art may be referred to. Here, the present invention provides a preparation method of the porous material:

[0017] In the metal organic framework structure, cobalt formate, nickel formate and magnesium formate are synthesized by solvent thermal reaction of cobalt nitrate hexahydrate, nickel nitrate hexahydrate, magnesium nitrate hexahydrate and organic ligand formic acid, and the solvent used is N,N-dimethylformamide; among them, cobalt formate and nickel formate react at 100℃ for 24h, and magnesium formate needs to react at 110℃ for 48h; manganese formate is synthesized by solvent thermal reaction of manganese chloride tetrahydrate and formic acid, and the solvent used is N,N-diethylformamide (DEF) and 1,4-dioxane, and the reaction is carried out at 120℃ for 72h;

[0018] After the solvothermal reaction is completed, the solid is filtered out, washed with anhydrous methanol, and soaked with anhydrous methanol to replace the solvent molecules in the pores of the material to obtain the porous material.

[0019] In a second aspect, the present invention provides a shaped porous material prepared by the preparation method described in the first aspect.

[0020] In a third aspect, the present invention provides use of the porous material described in the first aspect and / or the shaped porous material described in the second aspect in the adsorptive separation of ethylene and propylene.

[0021] In a fourth aspect, the present invention provides a method for separation of ethylene and propylene by adsorptive means, comprising: utilizing the porous material described in the first aspect and / or the shaped porous material described in the second aspect to selectively adsorb propylene in a mixture containing ethylene and propylene, thereby separating ethylene and propylene.

[0022] In the method for separation of ethylene and propylene by adsorption described in the fourth aspect, the adsorption temperature may be 278 to 308 K, and the adsorption pressure may be 0 to 1 bar.

[0023] The method for separation of ethylene and propylene by adsorption described in the fourth aspect may adopt one or a combination of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption.

[0024] In some embodiments, the method for separation of ethylene and propylene by adsorption adopts fixed bed adsorption, including: the mixture containing ethylene and propylene flows through a fixed bed adsorption column filled with the porous material and / or the molded porous material, ethylene preferentially penetrates, and high-purity ethylene is directly obtained from the outlet of the fixed bed adsorption column.

[0025] In the method for separation of ethylene and propylene by adsorptive separation described in the fourth aspect, the molar ratio of propylene to ethylene in the mixture containing ethylene and propylene may be 1:1-9.

[0026] In some preferred embodiments, in the third aspect and the fourth aspect, the porous material and / or the molded porous material is first subjected to a vacuum activation treatment before the ethylene-propylene adsorption separation. Further, the vacuum pressure may be -0.01 to -0.1 MPa, the activation temperature may be 120°C, and the activation time may be 10 to 12 hours.

[0027] In the third and fourth aspects, the porous material and / or the molded porous material can be regenerated by heating vacuum desorption and other methods after adsorption to achieve recycling. After the separation of C3H6 / C2H4 is completed, C3H6 and C2H4 can be removed under the temperature and pressure conditions of 50-120°C and 0-1atm to achieve the regeneration of the porous material and / or the molded porous material. When the relative humidity RH=100%, the porous material and / or the molded porous material can still maintain excellent C3H6 and C2H4 separation performance, indicating that water vapor has little effect on the material; after 5 cyclic adsorption and desorption experiments, the material's production of C2H4 and the amount of C3H6 captured remain almost unchanged, indicating that the material has certain stability and recycling regeneration ability. The force between the porous material and / or the molded porous material and the gas molecules in the present invention is a physical force, and desorption and regeneration are easy.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention proposes a novel catalyst based on a cheap organic ligand formic acid (HCOOH) and a cheap metal inorganic salt (Ni 2+ 、Co 2+ Mg 2+ , Mn 2+ ) The ultra-microporous porous material synthesized by solvent thermal synthesis is used for separating ethylene and propylene, and specifically can be used for separating MTO products.

[0030] The raw materials of the porous material of the invention are formic acid and inorganic salt, the solvent is a cheap and commonly used organic reagent, the synthesis cost of the porous material is low, and the operation is simple.

[0031] The porous material of the present invention has a stronger adsorption capacity for C3H6 than C2H4. According to calculations using the ideal adsorption solution theory (IAST), the selectivity of the molded porous material Co3(HCOO)6 for C3H6 / C2H4 is 12 at 298K.

[0032] The porous material of the present invention has an excellent separation effect on the C3H6 / C2H4 / Ar mixed gas in a fixed bed penetration test, and can achieve the purpose of separating the MTO product.

[0033] The porous material of the present invention can achieve a high adsorption capacity and separation selectivity for C3H6. In a preferred embodiment, the adsorption capacity of the porous material (cobalt formate Co3(HCOO)6) for C3H6 can reach 0.65 g / mL, and the adsorption capacity of the porous material for C3H6 after granulation and molding remains almost unchanged. It can be seen that the porous material and / or molded porous material of the present invention has good application prospects in separating ethylene propylene and MTO products.

[0034] In summary, the present invention has the following advantages:

[0035] 1. The pore size of porous materials is approximately The abundant O sites on the surface can firmly adsorb propylene, showing the characteristics of a single-molecule adsorption trap and having an extremely high propylene stacking density.

[0036] 2. The synthesis cost of porous materials is low, the price is relatively cheap, and the preparation method is simple.

[0037] 3. The porous material has a stronger adsorption capacity for C3H6 than C2H4 and can effectively separate MTO products.

[0038] 4. Porous materials are easy to desorb and regenerate, and can be regenerated and reused.

[0039] 5. Porous materials have higher thermal stability.

[0040] 6. The porous material obtained by granulation molding technology not only maintains the separation effect of porous powder materials, but also alleviates the pipeline blockage problem caused by powder, so it is more suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram of the structure of a porous material of the present invention;

[0042] Figure 2 This is a photo of the adsorbent particles after forming in Example 5;

[0043] Figure 3 The single-component adsorption isotherms of C3H6 / C2H4 of the Co3(HCOO)6 porous material of Example 1 and the porous material CoF@5%PES formed according to Example 5 at 298K and 0-100kPa;

[0044] Figure 4 The adsorption isotherms of C3H6 of the Co3(HCOO)6 porous material of Example 1 and the porous material CoF@5%HPC formed according to Example 6 under the conditions of 298K and 0-100kPa;

[0045] Figure 5 The adsorption isotherms of C3H6 of the Co3(HCOO)6 porous material of Example 1 and the porous material CoF@5%PVB formed according to Example 7 under the conditions of 298K and 0-100kPa;

[0046] Figure 6 is a penetration curve of the mixed gas of C3H6 / C2H4 / Ar (volume ratio v:v=10 / 10 / 80) on Co3(HCOO)6 in Example 14, and the mixed gas flow rate is 2 mL / min;

[0047] Figure 7 It is a penetration curve of the mixed gas of C3H6 / C2H4 / Ar (volume ratio v:v=10 / 10 / 80) on the porous material CoF@5%PES after molding in Example 18, and the mixed gas flow rate is 2mL / min;

[0048] Figure 8 This is the thermogravimetric curve of the Co3(HCOO)6 porous material in Example 19 and the porous material after molding. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0050] Example 1

[0051] Co(NO3)2·6H2O (52.36 g), formic acid (30 mL), and 300 mL DMF were added to a 500 mL round-bottom flask, reacted at 100°C for 24 hours, cooled to room temperature, filtered, and washed with anhydrous methanol to obtain a pink powder, which was vacuum dried. The yield was calculated to be about 92%; the above product was soaked in anhydrous methanol and the anhydrous methanol was replaced every six hours for more than 5 times to remove the solvent molecules in the pores of the material. The cheap porous material Co3(HCOO)6, referred to as CoF, was obtained.

[0052] Example 2

[0053] Add Ni(NO3)2·6H2O (30g), formic acid (30mL), and 300mL DMF to a 500mL round-bottom flask and react at 100℃ for 24h. Cool to room temperature, filter, and wash with anhydrous methanol to obtain a green powder. Soak the above product in anhydrous methanol and replace the anhydrous methanol every six hours for more than 5 times to remove the solvent molecules in the pores of the material. Obtain a cheap porous material Ni3(HCOO)6, referred to as NiF.

[0054] Example 3

[0055] Add MnCl2·4H2O (4g), formic acid (1.5mL), 8mL DEF, and 4mL 1,4-dioxane to a 20mL glass culture bottle, sonicate until dissolved, transfer the resulting clear solution to a 25mL reactor, and react at 120°C for 72h. Cool to room temperature and filter. Soak the resulting product in anhydrous methanol and replace the anhydrous methanol every six hours for more than five times to remove the solvent molecules in the pores of the material. Obtain a cheap porous material Mn3(HCOO)6, referred to as MnF.

[0056] Example 4

[0057] Mg(NO3)2·6H2O (7.7 g), formic acid (2.3 mL), and 10 mL DMF were added to a 20 mL glass culture bottle, and ultrasonicated until dissolved. The obtained clear solution was transferred to a 25 mL reactor and reacted at 110°C for 48 hours. Cooled to room temperature, filtered, and a colorless microcrystalline powder was obtained. The above product was soaked in anhydrous methanol and the anhydrous methanol was replaced every six hours for more than 5 times to remove the solvent molecules in the pores of the material, and a cheap porous material Mg3(HCOO)6, referred to as MgF, was obtained.

[0058] Example 5

[0059] 2.8g of powdered material Co3(HCOO)6 prepared according to Example 1, 150mg of polyethersulfone (PES) and 2mL of N,N-dimethylformamide were placed in a 20mL culture bottle and stirred for 3h to mix them evenly. The obtained suspension was loaded into a 5mL syringe, and the syringe was slowly pushed to allow the suspension to drip drop by drop at a uniform rate into 40mL of anhydrous methanol prepared in advance in a 100mL beaker. The suspension dripped into anhydrous methanol quickly turned into ellipsoidal particles with a size of about 2 to 3mm. Next, the spherical particles were collected by filtration. After drying, the molded particles were obtained, and CoF@5%PES particles with a mass fraction of 5% of the adhesive polyethersulfone were obtained. The photo of the molded adsorbent (i.e., molded porous material) particles is shown in the figure. Figure 2 shown.

[0060] The porous materials Ni3(HCOO)6, Mn3(HCOO)6 and Mg3(HCOO)6 prepared according to Examples 2 to 4 are used respectively to replace Co3(HCOO)6, and the corresponding shaped porous materials can be prepared according to the above method.

[0061] Example 6

[0062] 2.8g of powdered material Co3(HCOO)6 and 150mg of hydroxypropyl cellulose (HPC) prepared in Example 1 were placed in a mortar and mixed evenly. During the stirring process, 1mL of deionized water was added in small amounts and multiple times until a semi-dried solid mass was obtained. Next, 1-2mm particles were obtained through an extruder. After drying, molded particles were obtained, and CoF@5%HPC particles with a mass fraction of 5% of hydroxypropyl cellulose as an adhesive were obtained.

[0063] The porous materials Ni3(HCOO)6, Mn3(HCOO)6 and Mg3(HCOO)6 prepared according to Examples 2 to 4 are used respectively to replace Co3(HCOO)6, and the corresponding shaped particles can be prepared according to the above method.

[0064] Example 7

[0065] A wet granulation technique similar to that in Example 6 is used, specifically described as follows: 2.8 g of powdered material Co3(HCOO)6 and 150 mg of polyvinyl butyral (PVB) prepared in Example 1 are placed in a mortar and mixed evenly. During the stirring process, 1 mL of anhydrous ethanol is added in small amounts and multiple times until a semi-dried solid mass is obtained. Next, 1-2 mm particles are obtained through an extrusion device. After drying, molded particles are obtained, and CoF@5% PVB particles with a mass fraction of 5% polyvinyl butyral as an adhesive are obtained.

[0066] The porous materials Ni3(HCOO)6, Mn3(HCOO)6 and Mg3(HCOO)6 prepared according to Examples 2 to 4 are used respectively to replace Co3(HCOO)6, and the corresponding formed particles can be obtained according to the above method.

[0067] Example 8

[0068] The porous material in Example 1 and the corresponding molded adsorbent particles in Example 5 were activated at 120°C for 10 hours to obtain an activated porous material and a molded porous material for gas adsorption separation. The activated materials were tested for single-component adsorption isotherms of C3H6 and C2H4 at 298K ( Figure 3 ), under the condition of 1 bar, the saturated adsorption capacity of unformed Co3(HCOO)6 for C3H6 can reach 92.7 cm 3 / cm 3 The saturated adsorption capacity of C2H4 reaches 88 cm 3 / cm 3 At the same time, the saturated adsorption capacity of the formed particles CoF@5%PES for C3H6 and C2H4 is 88.76 cm 3 / cm 3 and 83.57cm 3 / cm 3 , indicating that the shaped porous material obtained by granulation can still maintain a high adsorption capacity of C3H6 and C2H4. Based on the ideal adsorption solution theory (IAST), the separation selectivity of C3H6 / C2H4 of the shaped particles is 12, and the separation selectivity of the unshaped Co3(HCOO)6 for C3H6 / C2H4 is 10, indicating that the porous material has a stronger adsorption capacity for C3H6 than C2H4, that is, it can be used to separate MTO products.

[0069] Example 9

[0070] The porous material in Example 2 and the corresponding molded adsorbent particles in Example 5 were activated by vacuum at 120°C for 10 hours to obtain the activated porous material and the molded porous material for gas adsorption separation. Next, through the single component adsorption test of C3H6 and C2H4, under the conditions of 1 bar and 298K, the saturated adsorption capacity of unmolded Ni3(HCOO)6 for C3H6 can reach 76.8 cm 3 / cm 3 The saturated adsorption capacity of C2H4 reached 72 cm 3 / cm 3 At the same time, the saturated adsorption capacity of the formed particles for C3H6 and C2H4 is 71.9 cm 3 / cm 3 and 68.3cm 3 / cm 3 , indicating that the shaped porous material obtained by granulation can still maintain a high adsorption capacity of C3H6 and C2H4. Based on the ideal adsorption solution theory (IAST), the separation selectivity of the shaped adsorbent particles NiF@5%PES for C3H6 / C2H4 is 11, and the separation selectivity of the unshaped Ni3(HCOO)6 for C3H6 / C2H4 is 10.

[0071] Example 10

[0072] The porous material in Example 3 and the corresponding molded adsorbent particles in Example 5 were activated by vacuum at 120°C for 10 hours to obtain the activated porous material and the molded porous material for gas adsorption separation. Next, through the single component adsorption test of C3H6 and C2H4, under the conditions of 1 bar and 298K, the saturated adsorption capacity of unmolded Mn3(HCOO)6 for C3H6 can reach 75.2 cm 3 / cm 3 The saturated adsorption capacity of C2H4 reached 72.4 cm 3 / cm 3 At the same time, the saturated adsorption capacity of the formed particles for C3H6 and C2H4 is 71.6 cm 3 / cm 3 and 67.5cm 3 / cm 3 , indicating that the shaped porous material obtained by granulation can still maintain a high adsorption capacity of C3H6 and C2H4. Based on the ideal adsorption solution theory (IAST), the separation selectivity of the shaped adsorbent particles MnF@5%PES for C3H6 / C2H4 is 10, and the separation selectivity of the unshaped Mn3(HCOO)6 for C3H6 / C2H4 is 8.

[0073] Embodiment 11

[0074] The porous material in Example 4 and the corresponding molded adsorbent particles in Example 5 were activated by vacuum at 120°C for 10 hours to obtain the activated porous material and the molded porous material for gas adsorption separation. Next, through the single component adsorption test of C3H6 and C2H4, under the conditions of 1 bar and 298K, the saturated adsorption capacity of unmolded Mg3(HCOO)6 for C3H6 can reach 74.8 cm 3 / cm 3 The saturated adsorption capacity of C2H4 reached 68.5 cm 3 / cm 3 At the same time, the saturated adsorption capacity of the formed particles for C3H6 and C2H4 is 69.3 cm 3 / cm 3 and 64cm3 / cm 3 , indicating that the shaped porous material obtained by granulation can still maintain a high adsorption capacity of C3H6 and C2H4. Based on the ideal adsorption solution theory (IAST), the separation selectivity of the shaped adsorbent particles MgF@5%PES for C3H6 / C2H4 is 12, and the separation selectivity of the unshaped Mg3(HCOO)6 for C3H6 / C2H4 is 9.

[0075] Example 12

[0076] The porous material in Example 1 and the corresponding molded adsorbent particles in Example 6 were activated by vacuum at 120°C for 10 hours to obtain the activated porous material and the molded porous material for gas adsorption separation. Next, the single component adsorption test of C3H6 was performed. The adsorption results are shown in Figure 4 At 1 bar and 298 K, the adsorption capacity of CoF@5%HPC on C3H6 is only 4 cm 3 / cm 3 , indicating that the use of adhesive HPC will cause Co3(HCOO)6 to lose its adsorption capacity for C3H6.

[0077] Example 13

[0078] The porous material in Example 1 and the corresponding molded adsorbent particles in Example 7 were activated by vacuum at 120°C for 10 hours to obtain the activated porous material and the molded porous material for gas adsorption separation. Next, the single component adsorption test of C3H6 was performed. The adsorption results are shown in Figure 5 Under the conditions of 1 bar and 298 K, the adsorption amount of C3H6 by the molded CoF@5%PVB decreased to 41.7 cm 3 / cm 3 , the adsorption amount of CoF@10%PVB for C3H6 decreased to 35.1cm 3 / cm 3 , indicating that the use of adhesive PVB will cause the pores of Co3(HCOO)6 to be blocked.

[0079] Embodiment 14

[0080] The ultra-microporous porous material Co3(HCOO)6 obtained in Example 1 was placed in an adsorption column (4.6 mm×10 cm), and vacuum activated at 120°C for 10 hours. At 25°C, a mixed gas of C3H6 / C2H4 / Ar (volume ratio 10 / 10 / 80) was passed into the adsorption column at 2 mL / min. The separation results are shown in Table 1. Figure 6When C3H6 / C2H4 / Ar (volume ratio 10 / 10 / 80), C2H4 first penetrates the penetration column, indicating that Co3(HCOO)6 has the ability to separate C3H6 and C2H4.

[0081] Embodiment 15

[0082] The ultra-microporous porous material Ni3(HCOO)6 obtained in Example 2 was loaded into an adsorption column (4.6mm×10cm), and vacuum activated at 120°C for 10 hours. At 25°C, a mixed gas of C3H6 / C2H4 / Ar (volume ratio of 10 / 10 / 80) was passed into the adsorption column at 2mL / min. C2H4 first penetrated through the penetration column, indicating that Ni3(HCOO)6 has the ability to separate C3H6 and C2H4.

[0083] Example 16

[0084] The ultra-microporous porous material Mn3(HCOO)6 obtained in Example 3 was loaded into an adsorption column (4.6mm×10cm), and vacuum activated at 120°C for 10 hours. At 25°C, a mixed gas of C3H6 / C2H4 / Ar (volume ratio of 10 / 10 / 80) was passed into the adsorption column at 2mL / min. C2H4 first penetrated through the penetration column, indicating that Mn3(HCOO)6 has the ability to separate C3H6 and C2H4.

[0085] Embodiment 17

[0086] The ultra-microporous porous material Mg3(HCOO)6 obtained in Example 4 was loaded into an adsorption column (4.6mm×10cm), and vacuum activated at 120°C for 10 hours. At 25°C, a mixed gas of C3H6 / C2H4 / Ar (volume ratio of 10 / 10 / 80) was passed into the adsorption column at 2mL / min. C2H4 first penetrated through the penetration column, indicating that Mg3(HCOO)6 has the ability to separate C3H6 and C2H4.

[0087] Embodiment 18

[0088] The shaped porous material CoF@5% PES obtained in Example 5 was placed in an adsorption column (4.6 mm×10 cm), and vacuum activated at 120°C for 10 hours. At 25°C, a mixed gas of C3H6 / C2H4 / Ar (volume ratio 10 / 10 / 80) was introduced into the adsorption column at 2 mL / min. Figure 7 As shown, the penetration results similar to those of the unformed material CoF were obtained, that is, C2H4 first penetrated through the penetration column, indicating that the formed CoF@5%PES particles can maintain the separation effect of powdered CoF for C3H6 and C2H4.

[0089] The porous materials NiF@5%PES, MnF@5%PES and MgF@5%PES obtained in Example 5 were subjected to penetration tests according to the above method, and it was found that C2H4 first penetrated through the penetration column, and the separation effect of powdered NiF, MnF and MgF on C3H6 and C2H4 was maintained.

[0090] Embodiment 19

[0091] The porous material in Example 1 and the porous material formed in Example 5 were subjected to thermogravimetric testing. The thermal stability test results are shown in FIG. Figure 8 , the thermal stability of CoF and CoF@5%PES reaches about 290℃, indicating that the obtained materials have high thermal stability.

[0092] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a shaped porous material having ethylene and propylene adsorption and separation capabilities, characterized in that: include: The porous material, polyethersulfone and N,N-dimethylformamide are mixed and then transferred into anhydrous methanol to form a molded porous material by using a phase inversion method; The porous material is one or more metal organic framework materials with a general structural formula of M3(HCOO)6, wherein M is Ni, Co, Mg or Mn.

2. The preparation method according to claim 1, characterized in that: The amount of the polyethersulfone is 5% to 10% of the sum of the mass of the porous material and the polyethersulfone.

3. The shaped porous material prepared according to the preparation method according to claim 1 or 2.

4. Use of a porous material and / or a shaped porous material according to claim 3 in the adsorption separation of ethylene and propylene, characterized in that: The porous material is one or more metal organic framework materials with a general structural formula of M3(HCOO)6, wherein M is Ni, Co, Mg or Mn.

5. A method for separation of ethylene and propylene by adsorption, characterized in that: include: Using the porous material and / or the shaped porous material according to claim 3 to selectively adsorb propylene in the mixture containing ethylene and propylene to separate ethylene and propylene; The porous material is one or more metal organic framework materials with a general structural formula of M3(HCOO)6, wherein M is Ni, Co, Mg or Mn.

6. The method for separation of ethylene and propylene by adsorption according to claim 5, characterized in that: The adsorption temperature is 278~308K, and the adsorption pressure is 0~1bar.

7. The method for separation of ethylene and propylene by adsorption according to claim 5, characterized in that: The method for separating ethylene and propylene by adsorption adopts one or a combination of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption.

8. The method for separation of ethylene and propylene by adsorption according to claim 5, characterized in that: The method for separating ethylene and propylene by adsorption adopts fixed bed adsorption, comprising: the mixture containing ethylene and propylene flows through a fixed bed adsorption column filled with the porous material and / or the shaped porous material, ethylene preferentially penetrates, and high-purity ethylene is directly obtained from the outlet of the fixed bed adsorption column.

9. The method for separation of ethylene and propylene by adsorption according to claim 5, characterized in that: The molar ratio of propylene to ethylene in the ethylene-propylene mixture is 1:1-9.

Citation Information

Patent Citations

  • Method for adsorbing and separating cyclopentane and neohexane

    CN113527030A

  • Method for preferentially adsorbing and separating ethylbenzene from C8 aromatic hydrocarbon isomeride mixture

    CN114409498A